The role of United Nations envoys in conflict zones - A case study (Darfur) (2003-2024) - Abu Rumman, Hamza Khalaf (Journal of Humanities & Social Sciences, 2024)
The study aimed to explore the role of United Nations envoys in the conflict zone of Darfur from 2003 to 2024. Utilizing a descriptive analytical approach, the research relied on social surveys to collect data from a diverse group of analysts and experts to assess the effectiveness of the envoys in Darfur. The findings revealed that, despite being limited in effectiveness due to political and financial challenges, the interventions of the United Nations significantly contributed to improving the humanitarian situation and supporting peace efforts. However, the conflict persists due to ongoing internal and external issues. The results emphasized the crucial role that AUN envoys played in mediation and supporting humanitarian efforts and also highlighted the gaps between set goals and achieved outcomes, indicating significant challenges including logistical constraints and a lack of sustained support from international entities. The study recommends enhancing coordination mechanisms and improving diplomatic and humanitarian strategies to achieve a more sustainable impact in the region, urging the necessity of providing more financial and human resources to support the efforts of these envoys.
Keywords: Darfur; United Nations envoys; conflict zones; peace; humanitarian crisis; international interventions; internal conflict